Job Apathy: Scale Development and Initial Validation. (August 2017) - Schmidt, Gordon B.; Park, Guihyun; Keeney, Jessica; Ghumman, Sonia
Work anecdotes and popular media programs such as Office Space, The Office, and Dilbert suggest that there are a number of workers in the United States who feel a sense of apathy toward their workplace and their job. This article develops these ideas theoretically and provides validity evidence for a scale of job apathy across two studies. Job apathy is defined as a type of selective apathy characterized by diminished motivation and affect toward one's job. A scale of job apathy was developed and data from a sample of currently or recently employed college students supported two dimensions: apathetic action and apathetic thought. Job apathy was found to be empirically distinct from clinical apathy, negative affectivity, cynicism, and employee engagement. Job apathy was also found to have incremental validity in the prediction of personal initiative, withdrawal, and organizational deviance. Practical implications and future research directions for job apathy are discussed.